When Wetlands Dry: Feminist Political Ecology Study on Peat Ecosystem Degradation in South and Central Kalimantan - Catharina Indirastuti; Andi Misbahul Pratiwi (Jurnal Perempuan, 2019)
Indonesia tropical peatlands area is 47 percent of out of the total global peatlands. But unfortunately, sustainable peatland governance has not been widely applied in the management of peatlands, instead of being home to biodiversity, peatlands in Indonesia have ended up dry, burning and turned into monoculture plantations. The problem of peat ecosystem degradation is the result of unsustainable - historical environmental governance politics. This study shows the political complexity of peatland governance and its impact on women with a feminist political ecology lens. This research was conducted in several villages in Central and South Kalimantan, the largest tropical peat areas in Indonesia. This study found that 1) Rural women were realized that there are problems with peatland governance, both practically and politically; 2) women and girls have multiple impacts from peat ecosystem degradation ie, women are deprived of living space, women find it difficult to get water and food sources, women take over the role of the head of the family because men migrate but are not always recognized as the head of the family, and women are impoverished because they lose their independence and must work as oil palm workers. This study uses a feminist political ecology study as an analytical tool to see the multi-layered oppression experienced by rural women due to peat ecosystem degradation.